Poha Consumption and Glycemic Control: An Experimental Study - N.M. Jose (Medical Research and Its Applications Vol. 9, 2024)
Background of the Study: A research study on poha consumption and glycemic control was conducted with the objective of assessing the efficacy of glycemic control. The population included patients with type-2 Diabetes Mellitus. They were allowed to continue their normal life pattern during the addition of poha as a diet. Materials and Methods: A one-group pretest post-test design was used for the study. The sample size was 100. The setting was a selected village in Mangalore taluk in Dakshina Kannada district of Karnataka. The systematic sampling was used for the study. Results: The post-test GRBS levels of all the patients were lesser than the pretest levels after one week of pretest. The patients did not have any additional complaints. The study was significant and was tested at a 0.05 level. Conclusion: Poha is a part of the normal occasional diet in south India. Due to the ignorance of the glycemic control effect of this food, people do not consume it regularly. Because of the fiber content and slow release of glucose from the body, regular consumption of his food is very effective in controlling hyperglycemia. A large-scale awareness is to be created among the diabetic population regarding the efficacy of this food.